2018
DOI: 10.1016/j.cmet.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Impaired Glucose Metabolism in Women Are Predicted by Inefficient Subcutaneous Fat Cell Lipolysis

Abstract: Adipocyte mobilization of fatty acids (lipolysis) is instrumental for energy expenditure. Lipolysis displays both spontaneous (basal) and hormone-stimulated activity. It is unknown if lipolysis is important for future body weight gain and associated disturbed glucose metabolism, and this was presently investigated in subcutaneous adipocytes from two female cohorts before and after ≥10-year follow-up. High basal and low stimulated lipolysis at baseline predicted future weight gain (odds ratios ≥4.6) as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 58 publications
4
91
1
Order By: Relevance
“…Concordant with our current findings, lower nocturnal concentrations of plasma NEFAs during HFOF predict weight gain in obesity-prone individuals (33). Altogether, these results strongly point to a key role for lipolysis in obesity and body weight regulation (38,39).…”
Section: Discussionsupporting
confidence: 91%
“…Concordant with our current findings, lower nocturnal concentrations of plasma NEFAs during HFOF predict weight gain in obesity-prone individuals (33). Altogether, these results strongly point to a key role for lipolysis in obesity and body weight regulation (38,39).…”
Section: Discussionsupporting
confidence: 91%
“…This may depend on primary defects in gene expression of specific lipolytic regulators. 7 Aldosterone (ALDO) is a steroid hormone produced by the zona glomerulosa of the adrenal cortex and exerts its effects via mineralocorticoid receptor (MR). While classical effects of ALDO are mediated by MR expressed in renal epithelial cells, 8 MR has also been shown to play a key role in non-epithelial cells including adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it remains to be seen how extended periods of weight gain and frequent weight cycling in adulthood affect changes in total adipocyte number and turnover and influence energy metabolism. Interestingly, a recently published study by Arner et al [42] demonstrated that lipolysis is an important predictor of future weight gain and impaired glucose metabolism. Hence, similar prospective studies using an in vivo approach (i.e.…”
Section: Discussionmentioning
confidence: 99%